Quantification of Body-Reflected Neutron Doses in High-Energy Photon Radiotherapy Using an Albedo TLD Badge System - Musfika, Mst Ummey Habiba; Alim, Abdul; Rahman, Md Shakilur; Jamil, Hossen Mohammad; Meaze, AKM Moinul Haque; Siddiqua, Tanjim (Bangladesh Journal of Medical Physics, 2025)
This study aims to measure albedo neutron doses arising during high-energy photon radiotherapy, using an albedo TLD to check the spatial distribution and dose-dependency of these neutrons across a tissue-equivalent phantom. Irradiations were performed with a 15 MV medical linear accelerator. Alnor-type albedo TLD badges containing MTS-6 (6LiF, neutron and photon sensitive) and MTS-7 (7LiF, only photon sensitive) which were calibrated before Linac irradiation of an Alderson Rando phantom placing the badges at various anatomical sites. The design allows selective measurement of albedo neutrons by a dedicated window exposing a pair of MTS - 6 & 7 crystals, while others remain shielded by boron-loaded plastic. Dose measurements were performed at the lung center, right and left lungs, head-neck, and upper abdomen for delivered photon doses of 100, 200, and 300 cGy. Reflected neutron dose was highest at the beam center (lung center: 440.9 – 520.4 mSv) and decreased steeply at lateral (right/left lung: 33.0 – 66.8 mSv) and peripheral (head-neck, upper abdomen: 4.2 – 13.3 mSv) positions. At all locations, neutron dose increased linearly with delivered photon dose (R² ≈ 1). The dose at the peripheral regions confirms rapid spatial attenuation. The use of albedo TLD badge proves its effectiveness for distinguishing reflected neutrons from direct field and photon doses. Albedo neutrons contribute a measurable amount to total delivered dose particularly within and near the field. Routine assessment of albedo neutron dosimetry is recommended to ensure treatment quality. Ban. J. Med. Phys., Vol -16, Issue -1, 2025 : 7-10